The Role of Internet Based Learning in Promoting Self-Directed Learning Among Students in Islamic Education - Hamilaturroyya mila; Putri Ainur Rohmah; Uswatun Khasanah; Ahmad Zaki Mubarok; Muhammad Miftachurrachman (Jurnal At-Tarbiyat: Jurnal Pendidikan Islam, 2025)
The rapid development of internet technology has significantly transformed learning practices, highlighting the urgency of fostering self-directed learning (SDL) among students. This issue is particularly relevant in Islamic Religious Education (PAI), where digital media can potentially enhance student autonomy, critical reflection, and engagement. This study aims to explore the role of internet-based learning in promoting SDL among students at MTs Yaspi Pakis, Magelang. Using a qualitative case study approach, data were collected through in-depth interviews with teachers and students, participatory classroom observations, and document analysis. The data were analyzed using Miles and Huberman’s interactive model, including data reduction, presentation, and conclusion drawing. Findings indicate that while internet access and platforms such as Google, WhatsApp, and YouTube are widely utilized, students remain highly dependent on teacher guidance, exhibit limited motivation for independent exploration, and often use digital media for entertainment rather than academic purposes. Other barriers include low digital literacy, limited access to devices, lack of interactive digital content, weak parental support, and insufficient pedagogical design. The study concludes that internet-based learning alone does not guarantee increased autonomy in learning unless supported by improved digital literacy, interactive pedagogy, and collaboration among teachers, parents, and institutions. These findings contribute to the discourse on integrating technology into Islamic education by emphasizing the need for systemic interventions. Future research should explore broader contexts, employ mixed methods, and focus on developing innovative digital learning designs tailored to religious education.